2012
DOI: 10.1103/physreve.86.030101
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop liquid-vapor equilibrium in a one-component system

Abstract: We report Monte Carlo simulations that show a closed-loop liquid-vapor equilibrium in a pure substance. This finding has been achieved on a two-dimensional lattice model for patchy particles that can form network fluids. We have considered related models with a slightly different patch distribution in order to understand the features of the distribution of patches on the surface of the particles that make possible the presence of the closed-loop liquid-vapor equilibrium, and its relation to the phase diagram c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The thermodynamic stability at low T is shown to arise from the building up of non interacting clusters of particles with low energy and low entropy. The theory also provides a theoretical foundation of the behavior numerically observed recently in models of Janus particles in three dimensions [15] and in 2D-simulations of limited valence particles on lattice [21]. In both cases, the gas reentrance is connected to the self assembly into weakly or non interacting saturated aggregates (micelles for the Janus particles and rings for the patchy particles).…”
Section: Discussionmentioning
confidence: 99%
“…The thermodynamic stability at low T is shown to arise from the building up of non interacting clusters of particles with low energy and low entropy. The theory also provides a theoretical foundation of the behavior numerically observed recently in models of Janus particles in three dimensions [15] and in 2D-simulations of limited valence particles on lattice [21]. In both cases, the gas reentrance is connected to the self assembly into weakly or non interacting saturated aggregates (micelles for the Janus particles and rings for the patchy particles).…”
Section: Discussionmentioning
confidence: 99%
“…A related study of the generic phase diagram of 2A4B models on the triangular lattice with r > 1 3 , reports that orientational correlations between the A patches that promote ring formation have a profound effect on the phase equilibria. 18 No phase coexistence is observed when short rings are formed. Closed miscibility loops are found if larger rings are formed while the usual reentrant behavior is observed if no rings are formed.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the two cases α AB = 60 • and 80 • , it is clear that cycle formation decreases both the critical temperature T c and critical density ρ c . Lattice simulations 8 have also shown that cycle formation has a substantial influence on phase equilibria. Decreasing α AB further to α AB = 50 • , double bonding becomes significant which results in a further decrease in T c and ρ c as compared to the α AB = 60 • case.…”
Section: Resultsmentioning
confidence: 99%
“…There has also been an extensive number of theoretical and simulation studies on the thermodynamics, phase behavior, and self-assembly of patchy colloid fluids. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Patchy colloids are typically modeled using Wertheim's first order perturbation theory (TPT1) and a potential model for conical association sites introduced by Bol 22 and later Chapman 23 that became widely used in the patchy colloid community after Kern and Frenkel 24 introduced this potential as a primitive model for patchy colloids. a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%